The Impact of Running on Cardiovascular Health: A Comprehensive Review of Benefits and Risks - Bachoń, Emilia; Doligalska, Michalina; Stremel, Aleksandra; Wesołowska, Wiktoria; Leszyńska, Agnieszka; Iwańska, Martyna; Bałoniak, Zuzanna (Quality in Sport, 2024)
In recent years, running has become a very prevalent form of physical activity. Numerous studies indicate that it can have a beneficial effect on reducing the occurrence of cardiovascular disease (CVD). In this review, we look at the benefits and possible risks to the heart associated with running. Regular running can reduce the risk of all-cause death and improve heart and vascular function. The benefits from running are obtained by optimizing the dose of running to moderate levels. Running at high intensity or for long periods can cause problems such as heart tissue damage, arrhythmias, and exercise-induced hypertension (EIH), especially in middle-aged and older people. Marathons and ultra-endurance running (UER) are also associated with the risk of sudden cardiac death (SCD). This review discusses the latest information on the benefits and risks of running and examines the research on recreational running, marathons and, UER. This article aims to help people understand how running affects heart health and discusses the best amount of running to get the most health benefits while avoiding the negative effects. Information was collected from PubMed and Google Scholar.